ANALYSIS OF ASSOCIATION BETWEEN MALAT1 GENE RS619586-POLYMORPHISM AND DISEASE-FREE SURVIVAL IN KIDNEY CANCER AND BLADDER CANCER PATIENTS - Stroi, Yelizaveta (Eastern Ukrainian Medical Journal, 2025)
MALAT1 (Metastasis Associated Lung Adenocarcinoma Transcript 1) is an oncogenic long non-coding RNA, the overexpression of which is detected in many types of malignant tumors, including urinary tract cancer, and is often correlated with tumor progression and poor prognosis. Specific polymorphic loci within the MALAT1 gene are known to be associated with the development of urinary tract cancer and their impact on patient survival. Therefore, the aim of our work was to study the distribution of the MALAT1 rs619586-genotypes and alleles in patients with clear cell renal cell carcinoma (CCRCC) and transitional cell carcinoma of the urinary bladder (TCCUB), and to evaluate the potential association of this genetic locus with patient survival.Material and methods. The study included 342 individuals: 101 patients with ССRCC, 141 patients with TCCUB, and 100 cancer-free controls. Genotyping for the MALAT1 rs619586-locus was performed using real-time polymerase chain reaction (RT-PCR) with the TaqMan Assay C___1060479_10. Statistical analysis of the results was performed using the Prism (version 10.4.1) and R (version 4.4.2) software.Results. In CCRCC patients, the minor G-allele of the MALAT1 rs619586-polymorphism was significantly more frequent than in the control group (P = 0.03). No significant difference was found in the allele distribution for this locus among TCCUB patients (P = 0.09). A significant difference in the distribution of rs619586 genotypes was observed between men with CCRCC and male controls: carriers of the minor G-allele were more common among affected men (P = 0.01). Furthermore, among women with TCCUB, carriers of the minor G-allele were more frequent compared to female controls (P = 0.01). Sex-specific differences in the rs619586 genotype distribution were also revealed within the TCCUB group: female patients carried the minor allele more frequently than male patients (P = 0.0001). A decrease in survival was demonstrated in CCRCC patients who were carriers of the minor G-allele compared with major allele homozygotes (P = 0.0101). No association was detected between the MALAT1 rs619586-genotype and the overall survival of TCCUB patients (P = 0.8479).Conclusions. The minor G-allele of the MALAT1 rs619586-polymorphism is more frequent in CCRCC patients than in the control group. Furthermore, ССRCC patients carrying the G-allele exhibit lower survival rates compared to major allele homozygotes.